THE USE OF AUGMENTED REALITY MEDIA ON EARLY CHILDHOOD LANGUAGE SKILLS - Rahayu, Astira Sri; Hamzah Upu; Syamsuardi; Wahira; Herlina (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
Augmented Reality (AR)-based learning media offers innovative solutions that are able to overcome these challenges. AR can present learning content in an interactive and engaging way through the incorporation of digital visual elements into the real world. This research aims to implement the use of digital learning media in the hope of developing students' language skills and developing skills that can later be useful for students in facing global challenges in the world of education. The type of research used in this study is quantitative with an expost facto approach. The data collection techniques used are in the form of observation, test, and quantification techniques. The data analysis technique is a step in completing the research to test the data that has been collected, for example descriptive statistics and N-Gain effectiveness tests. The data obtained through research instruments is still in the form of raw data, so to analyze the data, the researcher uses statistical analysis. The collected data was analyzed using Simple Linear Regression Analysis with the help of IBM SPSS Statistics 25 software. The results of the study show that the implementation of augmented reality (AR) media has proven to be effective in developing early childhood language skills, as evidenced by descriptive analysis with an average AR media score of 79.40. These findings are in line with the research objective of utilizing digital learning media to equip children with essential communication skills to face global educational challenges, where score variations reflect individual heterogeneity but overall positive trends indicate the potential of AR as a contextual early childhood education innovation in Indonesia.